2019
DOI: 10.3390/healthcare7040154
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Health and Green Spaces in China: A Longitudinal Analysis of MMR Based on Spatial Panel Model

Abstract: The positive impact of green spaces on public health has attracted increasing attention, and maternal health has also been shown to be related to green spaces. However, there are different kinds of green space indicators that represent different mechanisms for mitigating maternal health, and few studies have investigated the different relevance amongst them with longitudinal data. This study explores the correlation between various green space indicators and maternal health using spatial panel models with prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Maternal health interventions, including access to high-quality care during pregnancy, delivery, and after childbirth, are considered highly effective in reducing the burden of maternal mortality and morbidity, particularly in low-resource settings [1,4,5]. Various factors contribute to access to quality maternal health services, from those well-documented, such as poverty, distance to health care facilities, access to information, quality health services, and cultural beliefs and practices [6], to those that have been identified most recently, including green space coverage [7]. However, it is important for local stakeholders to identify which barriers are most prevalent in their communities.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal health interventions, including access to high-quality care during pregnancy, delivery, and after childbirth, are considered highly effective in reducing the burden of maternal mortality and morbidity, particularly in low-resource settings [1,4,5]. Various factors contribute to access to quality maternal health services, from those well-documented, such as poverty, distance to health care facilities, access to information, quality health services, and cultural beliefs and practices [6], to those that have been identified most recently, including green space coverage [7]. However, it is important for local stakeholders to identify which barriers are most prevalent in their communities.…”
Section: Introductionmentioning
confidence: 99%
“…The seven longitudinal cohort studies recruited 133,363 participants, whereas the remaining 13 cross-sectional studies recruited a total of 202 million citizens. These studies were conducted in China (6 studies), 31,[37][38][39][40][41] Japan (3 studies), [42][43][44] Hong Kong (2 studies), 29,45 South Korea (2 studies), 46,47 Taiwan (2 studies), 48,49 and New Zealand (2 studies). 50,51 One study each was reported from Thailand, 52 Vietnam, 53 and Australia.…”
Section: Peer Reviewmentioning
confidence: 99%
“…18 studies had participants of both genders. One study included only women 38 and another included only men. 30…”
Section: Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…General health is affected by personal, socioeconomic, and environmental factors [6]. Further, body-mass-index (BMI) is associated with greenness and the presence of nature [7].…”
Section: Neighborhood Greenness Obesity and Physical Activitymentioning
confidence: 99%